3x+5+3x-6=10x-2

Simple and best practice solution for 3x+5+3x-6=10x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+5+3x-6=10x-2 equation:


Simplifying
3x + 5 + 3x + -6 = 10x + -2

Reorder the terms:
5 + -6 + 3x + 3x = 10x + -2

Combine like terms: 5 + -6 = -1
-1 + 3x + 3x = 10x + -2

Combine like terms: 3x + 3x = 6x
-1 + 6x = 10x + -2

Reorder the terms:
-1 + 6x = -2 + 10x

Solving
-1 + 6x = -2 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-1 + 6x + -10x = -2 + 10x + -10x

Combine like terms: 6x + -10x = -4x
-1 + -4x = -2 + 10x + -10x

Combine like terms: 10x + -10x = 0
-1 + -4x = -2 + 0
-1 + -4x = -2

Add '1' to each side of the equation.
-1 + 1 + -4x = -2 + 1

Combine like terms: -1 + 1 = 0
0 + -4x = -2 + 1
-4x = -2 + 1

Combine like terms: -2 + 1 = -1
-4x = -1

Divide each side by '-4'.
x = 0.25

Simplifying
x = 0.25

See similar equations:

| 2=1.2+-0.2y | | 30x+5=64 | | 1=1.2+-0.2y | | 42x^2-480x-2463=0 | | 120+.30x=80+.50x | | x+2y-1=6x-9 | | -4m+13=9 | | 3+6cosx=0 | | u^2+u-21=0 | | -6m-13=163 | | 6+0.4x=18+.02 | | 4(-2m-5)+8m=-15 | | 287+49m+7n=-64+4m-2n | | 322-(-159)+10-159+78= | | 39x^2-482x-2464=0 | | X+(x+3)=61 | | 2x-4=3x+12 | | .06+.04x=18+.02 | | 8(b+7)=0 | | y=-4*-4+2*-4-7 | | 36y^7+4y^4= | | 4.5/g+2=3/0.5g-1 | | 12-5+x=5+8-2 | | 8x+2y+2=180 | | (2x+7)=87 | | 5d-4(d-9)=3d-(9-d) | | 3.5t+8=2.25t-16 | | 0.92x+.98(12-x)=.96(12) | | 3x^2-12x+165=180 | | y=-5*5+2*-3-7 | | 9n=3(n-2) | | 3x^2-12+165=180 |

Equations solver categories